Improving Mathematical Literacy Ability of Elementary School Students Through A Field Trip Learning - Sita Husnul Khotimah; Agus Setyo Budi; Mohamad Syarif Sumantri (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractThis study aims to improve the mathematical literacy ability of elementary school students by using field trip in mathematics learning. This research tried to find out the general description of field trip starting from planning, implementation and evaluation. The object of field trip is adjusted to the mathematical material so that it gives an effect on students' mathematical literacy. The mathematical material used in this study is rounding and scale. The research design used for the trial was One Group Pretest-Posttest Design, by using n-gain test for data anlysis. Data collection is done through mathematical literacy tests and observations of student activities. The results showed an increase in mathematical literacy ability through the post-test and pretest. The first post-test obtained an increase of 54.48% and the second post-test 8.30%. The results of the N-Gain analysis showed the mathematical literacy ability of students in the rounding material and the scale increases from the first pretests of 0.7 and the second pretest of 0.77, of the two results indicate N-gain in the high category so that mathematics learning through the field trip can improve students' mathematical literacy effectively.Keywords: field trips, mathematical literacy, mathematics learning.AbstrakPenelitian ini bertujuan untuk meningkatkan kemampuan literasi matematis siswa Sekolah Dasar dengan menggunakan field trip pada pembelajaran matematika. Penelitian ini mencoba untuk menemukan gambaran umum tentang implementasi field trip mulai dari perencanaan, pelaksanaan, dan evaluasi. Lokasi field trip yang dituju disesuaikan dengan materi matematika, sehingga memberikan efek dalam literasi matematis siswa. Materi matematika yang digunakan dalam penelitian ini adalah materi pembulatan dan skala. Desain penelitian yang digunakan untuk uji coba adalah one group pretest-posttest design, dengan analisis data menggunakan uji n-gain. Pengumpulan data dilakukan melalui tes literasi matematis dan pengamatan aktivitas siswa. Hasil penelitian menunjukkan adanya peningkatan kemampuan literasi matematis dari hasil postes dan pretes. Postes pertama diperoleh peningkatan sebesar 54.48%, dan postes kedua 8.30%. Hasil analisis N-Gain menunjukkan kemampuan literasi matematis siswa dalam pembelajaran matematika pada materi pembulatan dan skala meningkat dari pretes-postes pertama sebesar 0.7 dan pretes-postes kedua sebesar 0.77, dari kedua hasil tersebut menunjukkan N-gain pada kategori tinggi sehingga pembelajaran matematika melalui field trip untuk meningkatkan literasi matematis efektif dalam penerapannya.Kata kunci: field trip, literasi matematis, pembelajaran matematika.